Education and hope: Stellenbosch University in the 21st century - Waghid , Y (South African Journal of Higher Education, 2011)
In the letter of invitation to the contributors to this special issue we wrote that A Pedagogy of Hope Revisited would be a collection of articles by members of the Faculty of Education at Stellenbosch University (SU). The intention was to help articulate a new vision and purpose for the Faculty’s education agenda while simultaneously contributing to debates on education in South Africa. In the letter a deep yearning was also expressed for the articulation of an education for social justice – one that focuses on the lives of our students and staff as persons who will assume the ethical, political and social responsibilities of our shared national and global communities.